2019
DOI: 10.1038/s41467-019-11014-1
|View full text |Cite
|
Sign up to set email alerts
|

A zwitterionic near-infrared fluorophore for real-time ureter identification during laparoscopic abdominopelvic surgery

Abstract: Iatrogenic injury of the ureters is a feared complication of abdominal surgery. Zwitterionic near-infrared fluorophores are molecules with geometrically-balanced, electrically-neutral surface charge, which leads to renal-exclusive clearance and ultralow non-specific background binding. Such molecules could solve the ureter mapping problem by providing real-time anatomic and functional imaging, even through intact peritoneum. Here we present the first-in-human experience of this chemical class, as well as the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…Despite finding uptake of PanLN-Forte in the liver and, to a lesser extent, in cartilage, these structures can be shielded during a surgical procedure, and are generally far away from the mesenteric LNs that play a relevant role in CRC LN metastasis (30). The optimal dose of 5 nmol translates to a human equivalent dose of 0.015 mg/kg, which is a low dose and similar to that of other recently clinically tested fluorophores for anatomic enhancement (31,32). Histologically, PanLN-Forte accumulated in the medulla of LNs suggesting direct uptake from the systemic circulation.…”
Section: Discussionmentioning
confidence: 97%
“…Despite finding uptake of PanLN-Forte in the liver and, to a lesser extent, in cartilage, these structures can be shielded during a surgical procedure, and are generally far away from the mesenteric LNs that play a relevant role in CRC LN metastasis (30). The optimal dose of 5 nmol translates to a human equivalent dose of 0.015 mg/kg, which is a low dose and similar to that of other recently clinically tested fluorophores for anatomic enhancement (31,32). Histologically, PanLN-Forte accumulated in the medulla of LNs suggesting direct uptake from the systemic circulation.…”
Section: Discussionmentioning
confidence: 97%
“…Tumor-directed imaging with NIR has drawn clinical interest as an approach to spatially localize tumor, guide diagnosis, aid surgical resection, and perhaps contribute to postoperative adjuvant therapy. Synergy of this nanotechnology with expanding development of intraoperative imaging instrumentation now facilitates translation of this important concept into the hospitals (de Valk et al, 2019;Tummers et al, 2015). • H. L. Xu, Yang, et al (2018) synthesized a theranostic liposome (QSC-Lip) integrated with superparamagnetic iron oxide nanoparticles, QDs and cilengitide into one platform to target glioma.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Near-infrared (NIR) fluorescence imaging is an evolving technique that enhances normal and tumor anatomy by creating visual contrast where none otherwise exists. Multiple clinical studies with NIR agents have already been reported for malignancies (ie, colorectal, pancreatic, and ovarian cancer), metastases (ie, liver and peritoneal), and vital structures, such as the biliary tract and ureters (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…cRGD-ZW800-1 is a novel NIR-targeted peptide, which consists of a cyclic pentapeptide (cRGD) conjugated to the 800 nm zwitterionic NIR fluorophore ZW800-1 (18). cRGD is a clinically well-known peptide that binds to integrins, such as avb6, which are expressed on tumor cells and tumor-associated vascular endothelium associated with neoangiogenesis (19).…”
Section: Introductionmentioning
confidence: 99%